HUBUNGAN PERMAINAN OUTBOUND DENGAN PERKEMBANGAN SOSIAL ANAK DI TAMAN KANAK-KANAK KECAMATAN PADANGSIDIMPUAN UTARA: THE RELATIONSHIP BETWEEN OUTBOUND GAMES AND CHILDREN'S SOCIAL DEVELOPMENT IN KINDERGARTEN IN NORTH PADANGSIDIMPUAN DISTRICT - Latifah, Rahmy; Marlina, Serli (Thufuli, 2021)
This study aims to determine the relationship between outbound games and children's social development in Kindergarten Kecamatan Padangsidimpuan Utara. The research method used is quantitative in the form of correlation with the sampling technique, namely by cluster sampling. The results of the study show that there is a relationship between outbound games and children's social development in Kindergarten Kecamatan Padangsidimouan Utara by 85%. It can be concluded that outbound games have a relationship with children's social development.